Anselm of Canterbury and the desire for the Word - Sweeney, Eileen C. (Eileen Carroll) (Catholic University of America Press, 2012)
Sweeney's study offers a comprehensive picture of Anselm's thought and its development, from the early, intimate, monastically based meditations to the later, public, proto-scholastic disputations. She reveals Anselm as a thinker as relentless in his exposure of ambiguity, paradox, and separation as in his pursuit of certainty, necessity, and unity.